Proyecto de factibilidad para la creación de una empresa de producción y comercialización de snack de papachina en la ciudad de Macas, cantón Morona, provincia de Morona Santiago, para el año 2017 - Morquecho Saldaña, Luis Antonio (2017)
The general objective of the project is. Carry out a feasibility project for the creation of a production and marketing company of potato snack in the city of Macas, Morona canton, province of Morona Santiago, for the year 2017. The same one that was developed by using the following methods. Scientific, inductive deductive and analytic-synthetic. The collection of information for the analysis of the demand was made through a survey directed to the population of the Morona canton, which included a total of 384 people. The analysis of the offer was made through a survey addressed to 3 snack food distributors in the Morona canton. The project consists of 5 stages. In the stage of the market study it was known that there is a potential demand of 46,935 people who consume snack, which represent 94%, of this total, 87% of the population that is 40,834 represent effective demand and 89% that is 37,159 would be the effective client of the company the study also determined that the per-capita consumption of the population is 93.6 snack bags of 50gr per year. While the study of the offer tells us that there is an offer of 194,000 snack bags of 50gr per year; when making the balance between supply and demand, it was determined that there is an unmet demand of 3,284,082 units. In the Technical Study it was determined that the company will have an installed capacity of 468,000 units of 50 g / year papachina snack bags; the company will work with 80% of its capacity during the first year and will increase this percentage gradually until reaching 90% of the installed capacity. The plant will be located in the province of Morona Santiago, Morona Canton, Rio Blanco Parish. In the organizational study it was determined that the company will have 5 hierarchical levels: Executive, executive, adviser, assistant, and operational. The company will be incorporated under the legal form of Limited Liability Company, its corporate name is LA FORTUNA Cía. Ltda .; Its term will be 10 years. The financial analysis yielded the following results: investments in fixed assets 66,890.13 deferred asset 2,373 and working capital of 7,582.69 giving a total of 76,845.82 US dollars. The financial evaluation shows that the project reaches a NPV of 9,740.22 32ethe IRR is 14.77%. Taking into account these data we can determine that the project is feasible from the technical, organizational, legal, financial and economic point of view. Finally once the feasibility of the project is determined, the execution of the project is recommended, and in this way contribute to the development of the Morona canton through the use of the raw material and the generation of employment.